IC 9420 Mechanical Excavation Systems (In Three Parts) 2. Stope Leach And Stope Autoclave Mineral Recovery Systems (The National Institute for Occupational Safety and Health (NIOSH), 1995)
In this U.S. Bureau of Mines report, in situ vat leach mineral recovery system concepts are described and cost compared with conventional mining and pad and autoclave leach processing systems. In the proposed systems, leachable ores are enclosed in place in reagent-impermeable in situ vat constructions. The ores are then rubbled and flood leached or flood oxidized and leached. The in situ vats are called stope leach or stope autoclave vessels. The report also proposes ore body-adjacent in situ vat constructions containing rechargeable processing stopes. A series of ore body-specific, innovative, and conventional mineral recovery systems case study designs are described and prefeasibility level costed. Based on a comparison of these prefeasibility level cost estimates, the proposed systems are determined to be economically competitive with conventional min¬eral recovery systems. The in situ vat leach mineral recovery systems concepts for leachable and refractory ores are developed around the drill-split narrow-vein and longwall mining methods described in part 1 of this Information Circular series.